Information structure and syntactic choices in Kelabit - Hemmings, CL (De Gruyter, 2024)
This paper investigates the role of information structure in determining three syntactic choices in the Kelabit language of Northern Sarawak: (1) voice choice within a symmetrical voice system, (2) word order within each voice construction and (3) differential case-marking of the undergoer voice (uv) actor. In each case, information structure is shown to be relevant: word order can be used to place focus before background information, nominative case is used for the uv actor when the actor is focused/contrasted and the undergoer is topic, and an unusual mapping between arguments and information structure roles (e.g. a focused actor or an undergoer topic) can trigger the choice of the respective voice construction. However, it is the relative prominence or unexpectedness of information that is important, rather than the status of the subject as topic or focus. Hence, there is no one-to-one link between particular grammatical functions and information structure roles. Instead, the different syntactic choices combine and interact to express information in context. This supports the view that prominence is relational and suggests that information structure is an important component of prominence in Western Austronesian.